Fermentation Profile and Probiotic-Related Characteristics of Bifidobacterium longum MC-42 - Anna V. Begunova; Irina V. Rozhkova; Olga A. Glazunova; Konstantin V. Moiseenko; Olga S. Savinova; Tatyana V. Fedorova (Fermentation, 2021)
This article presents new data on Bifidobacterium longum MC-42—a strain that has been actively used for the preparation of commercial dairy products in Russia for almost 40 years. It was demonstrated that this strain possesses high activities of β-galactosidase, α-glucosidase, and leucine arylaminidase; inhibits the growth of pathogens such as Salmonella typhimurium, Staphylococcus aureus, and Escherichia coli; and can efficiently remove cholesterol from the cultural medium. The resistance of B. longum MC-42 determined for 15 commonly used antibiotics was in agreement with those previously reported for Bifidobacterium spp. The absence of frequently transmittable antibiotic resistance genes in the genome and the lack of undesirable activity of β-glucuronidase proved the safe use of B. longum MC-42 as a probiotic and starter culture. Additionally, the impact of two growth-promoting additives—yeast extract or milk protein hydrolysate containing supplementation—on the B. longum MC-42 fermentation profile was assessed. The introduction of these additives increases the maximum attainable viable cell count by orders of magnitude, significantly changed the profile of aminopeptidase activities in extracellular extracts, and influenced the antioxidant and antihypertensive properties of the obtained fermented products.